Penurunan Kadar Tembaga (Cu) pada Limbah Cair Industri Elektroplating Menggunakan Cangkang Telur Ayam Potong Teraktivasi Termal - Ninis Dian Ratnasari; Anita Dewi Moelyaningrum; Ellyke Ellyke (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Copper (Cu) heavy metal is produced from electroplating industry in its liquid waste. Eggshell has 7.000-17.000 pores and CaCO3 that can be used as an adsorbent for adsorbing Cu. The purpose of this research was to analyze the differences of Cu levels between the liquid waste which was not given and which was given with broiler’s eggshell powder thermal activated at 600 0C in concentration of 20 g/l, 25 g/l, and 30 g/l at 90 minutes contact duration. Type of this re-search was a true experiment. The data were analyzed by using One Way Anova test at ? = 0,05. The results show significant differences of Cu levels between control and treatment groups (p-value<0,001). Broiler’s eggshell powder with 30 gr/l concentration gives the highest reduction of the Cu level, i.e.as much as 69,23 %. Broiler’s eggshell powder can be used as Cu adsorbent, but further research is needed to control the other variables, namely: adsorbate concentration, surface tension, and stirring time, in order to obtain the optimum adsorption conditions.